2018
DOI: 10.1038/s41598-018-27728-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium electroporation on tumour vasculature

Abstract: Calcium electroporation (CaEP) is a novel anti-tumour treatment that induces cell death by internalization of large quantities of calcium. The anti-tumour effectiveness of CaEP has been demonstrated in vitro, in vivo, and in preliminary clinical trials; however, its effects on the vasculature have not been previously investigated. Using a dorsal window chamber tumour model, we observed that CaEP affected to the same degree normal and tumour blood vessels in vivo, as it disrupted the vessels and caused tumour e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 51 publications
6
43
0
Order By: Relevance
“…There was no effect of treatment with calcium alone in concentrations up to 5 mM [18,77,[80][81][82] and even up to 20 mM in the two cell lines where such high concentrations were tested [78]. This is unlike treatment with bleomycin alone where some effect is seen; however, this effect is much less than when combined with electroporation [81,84].…”
Section: Effect On Cancer Cells In Vitro and In Vivomentioning
confidence: 83%
See 1 more Smart Citation
“…There was no effect of treatment with calcium alone in concentrations up to 5 mM [18,77,[80][81][82] and even up to 20 mM in the two cell lines where such high concentrations were tested [78]. This is unlike treatment with bleomycin alone where some effect is seen; however, this effect is much less than when combined with electroporation [81,84].…”
Section: Effect On Cancer Cells In Vitro and In Vivomentioning
confidence: 83%
“…Calcium electroporation has been tested in vitro in 18 different cell lines (12 cancer cell lines and six normal cell lines of which five are immortalized cells and one is primary cells) [18,[77][78][79][80][81][82][83]. In all tested cell lines, calcium electroporation induced cell death in a dose-dependent manner [18,77,78,80,81] with an IC 50 ranging from 0.4-5.0 mM calcium (in combination with electroporation) in the studies where IC 50 was determined [80,81]. Similar effects can be reached with calcium electroporation as with electrochemotherapy using bleomycin, but no synergistic effect is seen when combining calcium and bleomycin before electroporation [84].…”
Section: Effect On Cancer Cells In Vitro and In Vivomentioning
confidence: 99%
“…The features of Ca-EP are very similar to ECT: they are both selective to tumour cell, the same pulsing conditions can be used for both procedures, and both have an anti-angiogenic effect in vitro and in vivo on both normal and tumour blood vessels [9,10]. It has also been demonstrated that Ca-EP initiates a systemic immune response.…”
Section: Introductionmentioning
confidence: 94%
“…Trials using calcium electroporation both in vivo, in vitro, and in clinical trials have demonstrated cell necrosis on different tumor histologies . Additionally, recent studies testing calcium electroporation on different tumor lines against normal cells showed an increased effect on tumor cells indicating that normal tissue surrounding the tumor would be less affected by the treatment .…”
Section: Introductionmentioning
confidence: 99%
“…20 Trials using calcium electroporation both in vivo, in vitro, and in clinical trials have demonstrated cell necrosis on different tumor histologies. 1,18,21,22 Additionally, recent studies testing calcium electroporation on different tumor lines against normal cells showed an increased effect on tumor cells indicating that normal tissue surrounding the tumor would be less affected by the treatment. 20,[23][24][25][26] A new clinical trial randomizing calcium electroporation against ECT on small skin metastases has shown calcium electroporation to have a similar objective response rate compared to ECT with only limited side effects.…”
Section: Introductionmentioning
confidence: 99%